RESPONS KUMBANG AMBROSIA TERHADAP PERLAKUAN DENG AN PESTISIDA - Paimin Sukartana; Abdurahim Martawijaya; Dominicus Martono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
A case study on the behavioral responses of ambrosia beetles to some pesticidal formulations was carried out at a logging area in West Kalimantan in 1981. Each pesticide formulation was sprayed to debarked logs of fresh1% felled ramin trees (Gonystylus bancanus Kurz.. The tested logs were, then, allowed for the beetle infestations for four weeks, and inspections were conducted weekly to count the beetle tunnels. A lower intensity of the beetle infestation on the treated logs than those on the controls was considered as an inhibitory response. in contrast, a higher intensity of the infestation on the treated logs was indicatively caused by a stimulatory response. These following conclusions are drawn from this study: 1. A highly inhibitory response on the ambrosia beetle attacks was shown by treatments with pesticide containing 50% cypermethrin or 50% fenithrotion.2. Ramin logs treated with pesticide containing either 30% TCMTB or a mixture of 90% thiourea + 10% quarternary ammonium + 0.1 % diazenium dioxy seemed to be highly stimulating to the beetles. The stimulating effect of the second formulation initially decreased and lost afterwards if the diazenium dioxy component was increased by 0.1 to 0.2%. A doubtful record was shown if the TCMTB was mixed with 2% borax.3. The pesticide containing 5% Cu-8-oxyquinolinolate and 80% dichlofluanid were also unaffected to the beetle responses